Pengaruh Audit Internal, Budaya Organiasai, dan Komite Audit Terhadap Pelaksanaan Good Corporate Governance pada PT Pos Indonesia Cabang Metro - Septiani, Asih; Hendri, Nedi; Padwa Sari, Gustin (Universitas Muhammadiyah Metro, 2024)
This study aims to examine the influence audit, organizational culture, audit committee on the emplementation of good corporate governance at PT Pos Indonsia Metro Branch. The type research used in this research is quantitative. In this study primary data was used throught quesetionnaires and the sample populations used was 66 employees in the company. The analytical tool used is multiple liner regression analysis using the IBM SPSS 22. The result of this study show internal audit has an influence on the implementation of good corporate governance, organizatioanal cilture influences the implementation of good corporate governnace, the audit committee influences the implemantations of good corporate governance and internal audit, Organizatioanal cilture, audit committee jointly influnces in the implementation of good corporate gobvernance, together with internal audit, Organizatioanal cilture, audit committee support the implemantations of good corporate governance